Respuestas

2012-08-16T17:39:21+02:00

x+y=-2

2x-2y=-1

despejamos x en 1                   igualo las ecuacione si x=x           reemplazo y en 1

x+y=-2                                      -2-y=2y-1/2                                x+y=-2

x=-2-y                                      2(-2-y)=1(2y-1)                           x+(-3/4)=-2

despejamos x en 2                   -4-2y=2y-1                                  x-3/4=-2

2x-2y=-1                                  -2y-2y=-1+4                                x=-2+3/4

2x=2y-1                                   (-4y=3)(-1)                                  x=-5/4 //respuesta

x=2y-1/2                                  4y=-3

                                               y=-3/4